2013
DOI: 10.1155/2013/840134
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin Increases Nonrapid Eye Movement Sleep via Adenosine Receptors in Rats

Abstract: Cordycepin (3′-deoxyadenosine) is a naturally occurring adenosine analogue and one of the bioactive constituents isolated from Cordyceps militaris/Cordyceps sinensis, species of the fungal genus Cordyceps. It has traditionally been a prized Chinese folk medicine for the human well-being. Because of similarity of chemical structure of adenosine, cordycepin has been focused on the diverse effects of the central nervous systems (CNSs), like sleep regulation. Therefore, this study was undertaken to know whether co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…The signal of EEG was measured for 6 hours between 11:00 am and 5:00 pm. Each group has 5–6 rats ( Hu et al ., 2013 ).…”
Section: Animal Surgery and Eeg Recordingmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal of EEG was measured for 6 hours between 11:00 am and 5:00 pm. Each group has 5–6 rats ( Hu et al ., 2013 ).…”
Section: Animal Surgery and Eeg Recordingmentioning
confidence: 99%
“…However, cordycepin ( Cordyceps militaris/sinensis ) increased theta waves power density during NREM sleep. Adenosine receptors (AR) subtypes (A1, A2A and A2B) were over-expressed by cordycepin, and they are showing non-specific AR activation ( Hu et al ., 2013 ).…”
Section: Natural Products Which Have Proven To Be Effective For Sleepmentioning
confidence: 99%
“…11,12) In this study, we first reported that cordycepin inhibited the level of TSLP by down-regulating caspase-1, RIP2, IKKβ, and NF-κB signal cascade in activated mast cells.…”
Section: Discussionmentioning
confidence: 91%
“…Other beneficial effects of 3’-dA, such as the anti-viral and anti-fungal effects, may also provide additional benefits to depressed patients, because viral or fungal infections contribute to or even cause depressive symptoms ( Tuli et al, 2013 ). 3’-dA also improves the quality of sleep by increasing non-rapid eye movement sleep ( Hu et al, 2013 ). Therefore, 3’-dA is considered relatively safe and beneficial for use as a potential novel antidepressant drug.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3’-deoxyadenosine (3’-dA, Cordycepin), one of the major bioactive metabolites in the Cordyceps Militaris ( Tuli et al, 2013 ), exerted a beneficial effect in a 6-week chronic unpredictable mild stress (CUMS) mouse model via the forced swim test (FST; Tianzhu et al, 2014 ). 3’-dA possesses a wide range of beneficial effects of therapeutic potential, including anti-insomnia, anti-inflammatory, anti-cancer, anti-viral, and anti-fungal activities ( Hu et al, 2013 ; Tuli et al, 2013 ). However, whether or not 3’-dA has a fast-acting antidepressant effect remains unknown.…”
Section: Introductionmentioning
confidence: 99%